2014
DOI: 10.1111/fcsr.12066
|View full text |Cite
|
Sign up to set email alerts
|

Fashion Influences between Mothers and Daughters: Exploring Relationships of Involvement, Leadership, and Information Seeking

Abstract: Mother‐daughter pairs were surveyed to explore their fashion influences on one another and to investigate the interrelated roles of their Fashion Involvement, Fashion Leadership, Opinion Leadership, and Information Seeking behaviors. Mothers and daughters agreed on the level of fashion influence that mothers have on daughters, but daughters perceived that they had more fashion influence on mothers than mothers reported. Additionally, levels of Fashion Involvement, Fashion Leadership, and Opinion Leadership dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Previous consumer studies discussed that trust is one of the important elements contributing to fashion communication between mothers and daughters. In Kestler and Paulins’ () study, mothers’ trust in their daughters’ fashion knowledge was a key factor that led mothers to follow their daughters’ fashion advice. Ruvio et al () reported that the more mothers perceived their daughters’ expertise on fashion to be credible, the more they relied on their daughters as fashion role models.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous consumer studies discussed that trust is one of the important elements contributing to fashion communication between mothers and daughters. In Kestler and Paulins’ () study, mothers’ trust in their daughters’ fashion knowledge was a key factor that led mothers to follow their daughters’ fashion advice. Ruvio et al () reported that the more mothers perceived their daughters’ expertise on fashion to be credible, the more they relied on their daughters as fashion role models.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Most of them have focused on mothers’ fashion influence on daughters. The influence of daughters on mothers’ clothing consumption patterns has only just begun to garner researchers’ attention (Gavish, Shoham, & Ruvio, ; Kestler & Paulins, ; Ruvio, Gavish, & Shoham, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As explained in the previous chapter, family and friends provide commentary on what to wear and specifically, mothers had an influence on what the women felt comfortable wearing. A plethora of research has studied the mother-daughter relationship and how it influences purchasing behavior (Minahan & Huddleston 2013, Minahan & Huddleston 2010, Kestler & Paulins 2014, indicating that this connection has a significant impact on conceptions of fashion and behaviors in the shopping process. As one study found, mothers did not necessarily dictate what women purchased, especially college-aged females; instead they were "monitoring appropriateness" of the outfits (Kestler & Paulins, 2014, p. 321).…”
Section: Rules Of the Game: Family Friends Fashion Magazinesmentioning
confidence: 99%